2018
DOI: 10.1186/s13567-018-0532-z
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and biologic comparisons of cyprinid herpesvirus 3 strains

Abstract: Cyprinid herpesvirus 3 (CyHV-3) is the archetypal fish alloherpesvirus and the etiologic agent of a lethal disease in common and koi carp. To date, the genome sequences of only four CyHV-3 isolates have been published, but no comparisons of the biologic properties of these strains have been reported. We have sequenced the genomes of a further seven strains from various geographical sources, and have compared their growth in vitro and virulence in vivo. The major findings were: (i) the existence of the two gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…Though KHV and CEV both infect and cause disease in carp, and its ornamental variety, koi (OIE, 2018;Way et al, 2017), KHV also infects goldfish and can cause disease in goldfish × carp hybrids (Bergmann et al, 2010;Hedrick, Waltzek, & McDowell, 2006). Mortality during epizootic events caused by these viruses can reach 100% (Haenen et al, 2016;Jung-Schroers et al, 2015;Way et al, 2017), though disease outcomes are influenced by water temperature and quality, population density, fish age and condition, as well as the breed of carp and viral genotype (Gao et al, 2018;Shapira et al, 2005;Thresher, Allman, & Stremick-Thompson, 2018;Uchii, Okuda, Minamoto, & Kawabata, 2013).…”
mentioning
confidence: 99%
“…Though KHV and CEV both infect and cause disease in carp, and its ornamental variety, koi (OIE, 2018;Way et al, 2017), KHV also infects goldfish and can cause disease in goldfish × carp hybrids (Bergmann et al, 2010;Hedrick, Waltzek, & McDowell, 2006). Mortality during epizootic events caused by these viruses can reach 100% (Haenen et al, 2016;Jung-Schroers et al, 2015;Way et al, 2017), though disease outcomes are influenced by water temperature and quality, population density, fish age and condition, as well as the breed of carp and viral genotype (Gao et al, 2018;Shapira et al, 2005;Thresher, Allman, & Stremick-Thompson, 2018;Uchii, Okuda, Minamoto, & Kawabata, 2013).…”
mentioning
confidence: 99%
“…Further molecular characterization of the Iraqi KHV was performed by PCR amplification and sequencing of Marker I and Marker II (Bigarré et al, 2009). Sequence analysis of Marker I showed that the Iraqi virus belongs to the Japanese lineage (J) according to Bigarré's classification (Bigarré et al, 2009), while Marker II sequences were similar to KHV M3 (MG925490-Belgium) recently described by Gao et al, (2018).…”
Section: Isolation Ofmentioning
confidence: 88%
“…KHV J and T formed one cluster, KHV-U, KHV-I and FL-BAC were in the same group while GZ11 are inconsistent in three trees and was interpreted as an intermediate status between European and Asian lineages. The phylogenetic tree based on full length genome sequences of 11 KHV strains was built using UPGMA in MEGA6 found that T, J and M3 are in Asian lineage, while strain KHV-U, E, I ,Cavoy, KHV-I ,FL, GZ11 and GZ11-SC in European Lineage (Gao et al, 2018). Our earlier research on comparison of TK gene of KHV strains showed that the strain GY01 close to the Asian lineage while in this report the GY01 was closer to KHV E and KHV-I which were normally regarded as European lineage.…”
Section: Multiple Alignment and Phylogenetic Analysis Of Gy01 And Othmentioning
confidence: 99%
“…Later multiple genome alignment of 11 KHV strains were made by MAFFT online and phylogenetic tree was constructed by UPGMA( unweighted pair group method with arithmetic means) which found that strain T, J,M3 were Asian lineage while other 7 including KHV-U,E,I,KHV-I,FL,Cavoy, GZ11 and GZ11-SC were European lineages (Gao et al, 2018). In a recent study in this laboratory a KHV strain GY1506 (available in GeneBank as KHV GY01, accession number MK260013,hereafter GY01) was isolated from diseased common carp in a farm in Jiangsu Province .The supernatant of the diseased fish tissue homogenate was inoculated into CCB cells.…”
Section: Introductionmentioning
confidence: 99%